Modulation of blood oxylipin levels by long-chain omega-3 fatty acid supplementation in hyper- and normolipidemic men - Schuchardt, Jan Philipp (2013)
INTRODUCTION: Long chain omega-3 polyunsaturated fatty acids (LC n-3 PUFA) such as EPA and DHA have been shown to possess beneficial health effects, and it is believed that many of their effects are mediated by their oxygenated products (oxylipins). Recently, we have shown that serum levels of several hydroxy, epoxy, and dihydroxy FAs are dependent on the individual status of the parent FAs in a cohort of normo- and hyperlipidemic subjects. So far, the effect of an increased dietary LC n-3 PUFA intake on hydroxy, epoxy, and dihydroxy FA levels has not been investigated in subjects with mild combined hyperlipidemia. SUBJECTS AND METHODS: In the present study, we compared oxylipin patterns of 10 hyperlipidemic (cholesterol >200 mg/dl; triglyceride >150 mg/ml) and 10 normolipidemic men in response to twelve weeks of LC n-3 PUFA intake (1.14 g DHA and 1.56 g EPA). Levels of 44 free hydroxy, epoxy and dihydroxy FAs were analyzed in serum by LC-MS. Additionally, oxylipin levels were compared with their parent PUFA levels in erythrocyte membranes; a biomarker for the individual PUFA status. RESULTS: Differences in the oxylipin pattern between normo- and hyperlipidemic subjects were minor before and after treatment. In all subjects, levels of EPA-derived oxylipins (170–4,800 pM) were considerably elevated after LC n-3 PUFA intake (150–1,400 %), the increase of DHA-derived oxylipins (360–3,900 pM) was less pronounced (30–130 %). The relative change of EPA in erythrocyte membranes is strongly correlated (r ≥ 0.5; p<0.05) with the relative change of corresponding epoxy and dihydroxy FA serum levels. The effect on arachidonic acid (AA)-derived oxylipin levels (140–27,100 pM) was inconsistent. DISCUSSION AND CONCLUSIONS: The dietary LC PUFA composition has a direct influence on the endogenous oxylipin profile, including several highly biological active EPA- and DHA-derived lipid mediators. The shift in oxylipin pattern appears to be dependent on the initial LC PUFA status particularly for EPA. The finding that also levels of other oxylipins derived from ALA, LA or AA are modified by LC n-3 PUFA intake might suggest that at least some of the effects of EPA and DHA could be mediated by a shift in the entire oxylipin profile.